If Mobilizing Educational Research Is the Answer, Who Can Afford to Ask the Question? An Analysis of Faculty Perspectives on Knowledge Mobilization for Scholarship in Education - Gustavo E. Fischman; Kate T. Anderson; Adai A. Tefera; Steven J. Zuiker (SAGE Publishing, 2018)
This article explores faculty perspectives at three colleges of education regarding strategies of knowledge mobilization for scholarship in education (KMSE), with consideration for the opportunities and challenges that accompany individual and organizational capacities for change. Faculty surveys ( n = 66) and follow-up interviews ( n = 22) suggest two important trends: First, KMSE presents both a complementary agenda and a competing demand; second, barriers and uncertainties characterize the relevance of knowledge mobilization for faculty careers in colleges of education. This study empirically illuminates the persistence of long-standing challenges regarding the relevance, accessibility, and usability of research in colleges of education housed in research-intensive universities. While KMSE holds promise for expanding the reach and impact of educational research, scholarly tensions underlying these trends suggest that individual and organizational efforts will suffice only with modifications to university procedures for identifying what counts as recognizable, assessable, and rewardable scholarly products and activities for faculty careers.